STRATEGI PROGRAM 3R (REDUCE, REUSE, RECYCLE) DALAM PENGELOLAAN SAMPAH DI KOTA TEMBILAHAN - Elma Susanti; Zulkarnain Zulkarnain; Viktor Amrivo (Program Pascasarjana Universitas Riau, 2017)
Negative impacts of waste become a problem especially in urban areas. Waste reduction can be implemented by increasing the role of the community through the 3R Program (Reduce, Reuse, Recycle). This study has been conducted from March to May 2017 in Tembilahan city using survey method and descriptive analysis. Data was collected by direct observation and interview to the research object in the form of current community behavior and government participation. This study aims to formulate the strategy of 3R Program in Tembilahan city by using SWOT-AHP analysis. The results showed that there were eight strategic alternatives according to importance weight priority in 3R Program strategy, namely: (a) optimizing TPST/TPS-3R for waste management; (b) disseminating the 3R Program effectively; (c) creating innovations in waste processing efforts; (d) empower communities in small scale waste processing industries; (e) Increase local government performance in waste management; (f) empower communities in the 3R Program; (g) establishing TPST/TPS-3R in each sub-district; and (h) controlling communities waste production. Therefore, good coordination among stakeholders related to the implementation of alternative strategies which has been formulated so that able to establish 3R Program based waste management in Tembilahan City.